Capability Coordination in Automobile Logistics Service Supply Chain Based on Reliability. (2016) - He, Meiling; Xie, Junping; Wu, Xiaohui; Hu, Qifan; Dai, Yu
Abstract: The paper builds a two-stage automobile Logistics Service Supply Chain (LSSC). The Logistics Service Integrator (LSI) is dominant. It integrates Functional Logistics Service Provider (FLSP). Considering the feature of non-storage and reliability, the buyback contract model was built under the stochastic demand. When the logistics capability that LSI wants to order is equivalent to FLSP willing to supply, the automobile LSSC reaches equilibrium. Compared with no contract, the buyback contract can coordinate the automobile LSSC better. Simulation results indicate that if the reliability increases, the optimal logistics capability order quantity, the buyback price and all expected profits decrease. If the penalty cost increases, the buyback price, the expected profits of LSI and LSSC decrease, while the optimal logistics capability order quantity and the expected profit of FLSP increase. Compared to the penalty cost, the relevant indexes are more sensitive to the reliability.